2011
DOI: 10.1375/twin.14.6.495
|View full text |Cite
|
Sign up to set email alerts
|

The Child and Adolescent Twin Study in Sweden (CATSS)

Abstract: The Child and Adolescent Twin Study in Sweden (CATSS) is an ongoing longitudinal twin study targeting all twins born in Sweden since July 1, 1992. Since 2004, parents of twins are interviewed regarding the children's somatic and mental health and social environment in connection with their 9th or 12th birthdays (CATSS-9/12). By January 2010, 8,610 parental interviews concerning 17,220 twins had been completed, with an overall response rate of 80%. At age 15 (CATSS-15) and 18 (CATSS-18), twins and parents compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
365
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 258 publications
(371 citation statements)
references
References 54 publications
5
365
1
Order By: Relevance
“…Previous attrition analyses of differences between non‐responders and responders in the CATSS study, based on data from approximately 11 000 twins, have indicated that CATSS non‐responders more often belong to lower socioeconomic groups 47. Hypothetically, a family burdened with psychosocial problems may be less motivated to participate, which could explain some of the attrition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous attrition analyses of differences between non‐responders and responders in the CATSS study, based on data from approximately 11 000 twins, have indicated that CATSS non‐responders more often belong to lower socioeconomic groups 47. Hypothetically, a family burdened with psychosocial problems may be less motivated to participate, which could explain some of the attrition.…”
Section: Discussionmentioning
confidence: 99%
“…The Child and Adolescent Twin Study in Sweden (CATSS) is an ongoing longitudinal cohort study following all twins born in Sweden from 1992 and onwards, that started in 2004 47. All twin parents in the country are invited to participate in a telephone interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study started in 2004 and the response rate of the telephone interview was 80% (Anckarsäter et al, 2011). Interviewers from a professional company carried out the interviews after a brief introduction in child and adolescent psychiatry and twin research.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have demonstrated substantial overlap among specific NDPs (20,22,23,28), and Gillberg (38) has argued for more comprehensive assessment and treatment for children with NDPs than what the current diagnostic system allows. The current results might be seen as corroborating this argument, in that a general NDP factor appeared stronger in predicting bullying victimization than specific neurodevelopmental problems or diagnoses.…”
Section: The General Ndp Factor and Bully Victimizationmentioning
confidence: 99%